Fabrication of cationic polymer surface through plasma polymerization and layer-by-layer assembly. Issue 2 (25th January 2020) - Chen, Rui; Shi, Changgui; Xi, Yanhai; Zhao, Peng; He, Hailong
ABSTRACT: Titanium implants have been widely used for orthopedic and trauma surgery, while they often encounter the predicament of implant-associated infection, which leads to surgery failure. To address this issue, polycation surface coatings that are able to improve the antibacterial properties of implants have been developed. The objective of this study is to fabricate amine cationic polymer onto the surface of titanium alloys via a combination of plasma polymerization and layer-by-layer assembly and to investigate their antibacterial property after implantation. Titanium alloys were coated with poly(allylamine) (PAA) as the first polycationic monolayer via plasma polymerization. The obtained PAA-coated titanium alloys were then assembled with multilayers of anionic poly(sodium 4-styrenesulfonate) (PSS) and cationic poly(allylamine hydrochloride) (PAH) through layer-by-layer (LbL) self-assembly. Surface characterization using scanning electron microscopy, contact angle measurement, atomic force microscopy and X-ray photoelectron spectroscopy confirmed the successful multilayer coatings of PAA, PSS and PAH onto the surface of titanium alloys. Such amine cationic polymer-coated titanium alloys exhibited a negligible in vitro cytotoxicity, while showed an effective antibacterial property against Escherichia coli and Staphylococcus aureus . In addition, no neutrophil distribution was observed between the implanted amine cationic polymer-coated titanium alloys and tissues, which suggested in vivo antibacterial property. These multilayer coated titanium alloys were able to minimize the implant-related infection and showed a great promise for bioimplantation.